The - Steve Cropper (Oxford University Press, 2008)
Inter-organizational relations (IOR), the study of Strategic Alliances, Joint Ventures, Partnerships, Networks and other forms of relationship between organizations, is a field of study that has burgeoned over the last four decades, but is fragemented, drawing contributions from a wide variety of disciplines, theoretical bases, and sectoral interests. The Oxford Handbook of Inter-Organizational Relations provides a structured overview of the field. With contributions from leading international experts on their particular areas of expertise, it is an authoritative introduction to its research findings